Aplicattion of the scale Herth and correlations in hematopoietic stem cell-transplantation (Research, Society and Development, 2021)
Hope is defined as a positive outlook on the future, inspiring courage to face fear. Although not considered a form of cure, it motivates the patient to face the disease in a positive way. This study aims to assess the level of life expectancy of adult patients in the pre - hematopoietic stem cell transplantation period and its relationship with results within 100 days post-procedure. This is a descriptive observational study, with a quantitative approach and cross-sectional, carried out in an outpatient clinic specializing in the bone marrow transplant service, from April to December 2020. A sample of 82 patients participated in this study, being 38 (46%) collected Pre-Hematopoietic Stem Cell Transplantation (HSCT) and 44 (54%) Post-Hematopoietic Stem Cell Transplantation (HSCT), using the Herth Hope Scale (EEH). As for the results, the sample showed a level of hope considered high (41.9) points in the pre group, followed by the post group (40.7) points. It is concluded that patients undergoing pre- and post-transplant treatment had high levels of hope throughout the treatment process. However, it was shown that individuals who perform religious practice as a strategy to deal with the disease, showed high levels of hope. The data from this study indicate that it is relevant for nursing professionals to encourage care that estimulates the positive mechanisms of beliefs, increasing levels of hope.